2012
DOI: 10.1111/j.1834-7819.2012.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bonding application time on the microleakage of Class V sandwich restorations

Abstract: Background: The aim of this study was to assess the effect of bonding application time on the microleakage of Class V sandwich restorations. Methods: Eighty non-carious third molars were randomly divided into 16 groups. Two Class V cavities were prepared on the buccal and lingual surfaces of teeth. Three groups were restored with Fuji II GIC and treated with a total-etch bonding system (Stea ⁄ SDI) immediately after insertion, at 7 minutes and 15 minutes after mixing the glass ionomer cements (GICs). Another t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…[4,18,28,29] Retention in and penetration into pits and fissures, risk of isolated carious lesions, and the inherent properties of the materials are some of the factors that can affect the effectiveness of a sealant. [19,20,21] In the present study, fluoride-releasing materials interfered with the metabolic activity of the biofilm, confirming the antimicrobial activity of fluoride. [24] The model used in this study for prevention of demineralization might have contributed to the results found for the dental materials tested.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[4,18,28,29] Retention in and penetration into pits and fissures, risk of isolated carious lesions, and the inherent properties of the materials are some of the factors that can affect the effectiveness of a sealant. [19,20,21] In the present study, fluoride-releasing materials interfered with the metabolic activity of the biofilm, confirming the antimicrobial activity of fluoride. [24] The model used in this study for prevention of demineralization might have contributed to the results found for the dental materials tested.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have used different methodologies to compare the application of ionomeric and resinous materials to pits and fissures in an attempt to prevent demineralization. [17,[20][21][22] Therefore, in this study, a cavity preparation was performed to simulate the conditions of pits and fissures and the Knoop microhardness test was carried out to assess demineralization around the preparation margins after 48-hour biofilm formation. Knoop microhardness has been widely used for this purpose [18,23,24] and the S. mutans biofilm metabolic activity test, which can simulate oral conditions, has been used to replace cyclic pH.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Dye penetration is an established in vitro method for investigating marginal leakage along tooth-restoration interfaces and is generally assessed after cutting the teeth in the longitudinal direction. [181920] Various tracer dyes are available for microleakage studies and there appears to be no significant difference in tracer penetration among fuchsin, silver nitrate and methylene blue. [21] Methylene blue is one of the most common tracers and can be used at different concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Microleakage can be assessed by scanning electron microscope of dye penetration. Penetration of dye is an in vitro method to investigate marginal leakage over tooth restoration interfaces (12)(13)(14) . Different tracer dyes are available for micro leakage researches, while there is no important difference in penetration of tracer between them (15) .…”
Section: -Microleakagementioning
confidence: 99%